Wireless mobile communication and healthcare : Third International Conference, MobiHealth 2012, Paris, France, November 21-23, 2012, Revised Selected Papers - Nikita, Konstantina S.; Godara, Balwant (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2013)
This book constitutes the refereed proceedings of the Third International Conference on Wireless Mobile Communication and Healthcare, MobiHealth 2012, and of the two workshops: Workshop on Advances in Personalized Healthcare Services, Wearable Mobile Monitoring, and Social Media Pervasive Technologies (APHS 2012), and Workshop on Advances in Wireless Physical Layer Communications for Emerging Healthcare Applications (IWAWPLC 2012), all held in Paris, France, in November 2012. The 39 revised full papers presented were carefully reviewed and selected from 66 submissions. The papers are organized in topical sections covering wearable, outdoor and home-based applications; remote diagnosis and patient management; data processing; sensor devices and systems; biomedical monitoring in relation to society and the environment; body area networks; telemedicine systems for disease-specific applications; data collection and management; papers from the invited session "Implants"; papers from the IWAWPLC and APHS workshops.